The psychology of learning and motivation. - Ross, Brian H. (Psychology of learning and motivation, 2016)
Psychology of Learning and Motivation publishes empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning to complex learning and problem solving. Each chapter thoughtfully integrates the writings of leading contributors, who present and discuss significant bodies of research relevant to their discipline. Volume 64 includes chapters on such varied topics as causal reasoning, the role of affordances in memory, technology-based support for older adult communication in safety-critical domains and what edge-based masking effects can tell us about cognition.